Neonatal Abstinence Syndrome and Preterm Infants: A Look at Current Practice. (April 2021) - Armbruster, Debra; Schwirian, Caitlyn; Mosier, Ashley; Tam, Wai-Yin Mandy; Prusakov, Pavel
Abstract : Background/Significance: Intrauterine opioid drug exposure is associated with an increased risk of preterm birth. Preterm infants may not exhibit the same withdrawal symptoms as term infants diagnosed with neonatal abstinence syndrome (NAS). There are no current standards for how to screen, assess, or treat NAS in preterm infants. Purpose: This study explored the current state of practice for preterm infants born at less than 34 weeks of gestational age exposed to intrauterine opioids. Methods: This was a descriptive cross-sectional study of NAS practice in preterm infants born at less than 34 weeks of gestational age in neonatal intensive care units (NICUs) in the United States and Canada. The study was conducted May through September 2018. All respondents cared for preterm infants born at less than 34 weeks of gestational age exposed to intrauterine drugs. Results: There were 70 respondents representing 67 hospitals in the United States and 1 in Canada. Level III NICUs represented 69% of respondents. Ninety-three percent reported neonatal triggers for further evaluation. Review of maternal history and maternal urine testing was the most consistent practice across NICUs. A modified Finnegan scoring tool was used for both preterm and term infants. Morphine was reported as the most common first-line drug used for treatment. Implications for Practice: Great variability in NAS practice for preterm infants born at less than 34 weeks of gestational age across the multiple NICUs supports the need for a validated preterm infant assessment tool and development of appropriate treatment strategies. Implications for Research: Future research describing the NAS symptomatology of preterm infants born at less than 34 weeks of gestational age exposed to intrauterine opioids is warranted. Abstract : Supplemental Digital Content is Available in the Text.